2021
DOI: 10.1073/pnas.2108163118
|View full text |Cite
|
Sign up to set email alerts
|

Class-specific interactions between Sis1 J-domain protein and Hsp70 chaperone potentiate disaggregation of misfolded proteins

Abstract: Protein homeostasis is constantly being challenged with protein misfolding that leads to aggregation. Hsp70 is one of the versatile chaperones that interact with misfolded proteins and actively support their folding. Multifunctional Hsp70s are harnessed to specific roles by J-domain proteins (JDPs, also known as Hsp40s). Interaction with the J-domain of these cochaperones stimulates ATP hydrolysis in Hsp70, which stabilizes substrate binding. In eukaryotes, two classes of JDPs, Class A and Class B, engage Hsp7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 62 publications
6
30
0
Order By: Relevance
“…In contrast to ribonucleotide reductase whose stability depends on Ydj1 function, loss of Ydj1 does not impact Apn2 stability [ 28 ]. It is possible that Apn2 stability in yeast is additionally regulated by other semi-redundant co-chaperones such as Sis1, which has similar yet distinct roles in the cell as Ydj1 [ 39 , 40 , 41 , 42 ]. This may also explain why in our studies, DNAJA1 the mammalian homologue of Ydj1 does not appear to interact with APE2 ( Figure 3 A).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to ribonucleotide reductase whose stability depends on Ydj1 function, loss of Ydj1 does not impact Apn2 stability [ 28 ]. It is possible that Apn2 stability in yeast is additionally regulated by other semi-redundant co-chaperones such as Sis1, which has similar yet distinct roles in the cell as Ydj1 [ 39 , 40 , 41 , 42 ]. This may also explain why in our studies, DNAJA1 the mammalian homologue of Ydj1 does not appear to interact with APE2 ( Figure 3 A).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified this region as being important for the binding of co-chaperone proteins. The VEEVD sequence at the end of Hsp70/Ssa1 is critical interaction with DNAJB-type co-chaperones including Sis1 [4952]. However, there is also substantial evidence that the CTD is also important for the binding of Ydj1.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified this region as being important for the binding of co-chaperone proteins. The VEEVD sequence at the end of Hsp70/Ssa1 is critical for interaction with DNAJB-type co-chaperones including Sis1 [ 55 58 ]. However, there is also substantial evidence that the CTD is also important for the binding of Ydj1.…”
Section: Discussionmentioning
confidence: 99%